A review on ethnobotanical aspects of Artocarpus altilis (Park.) Fosberg (Syn: Artocarpus communis J.R.Forst. & G.Forst.) (Breadfruit) in Indonesia - Raihandhany, Reza (Generasi Biologi Indonesia, 2022)
Ethnobotany has a significant impact for discovering medicine and food. The practice which is applied by traditional communities about their relation with plants in daily life can lead to research by scientist in order to seek the evidence from the local knowledge. Artocarpus altilis or known sukun as its local name, is one of a plants which widely used in Indonesia. A. altilis belong to Moraceae or mulberry family. Literature review was carried out in this research on A. altilis utilization as traditional medicine, local food, and any other uses by the traditional communities throughout Indonesia. Result showed that A. altilis is used by the traditional communities in almost region of Indonesia start from Sumatera, Java, Madura, Nusa Tenggara, Kalimantan, Sulawesi, Maluku, and Papua except Bali. A. altilis is used as traditional medicine. Leaf is the most used part and the way these traditional communities process the medicine by boiling the leaf of A. altilis. Other plant part like fruit, root, and bark are also utilized as materials for traditional medicine. Some research support the use of A. altilis as medicine. However, in Indonesia the consumption of A. altilis is just as a snack food, served by frying it called ‘keripik sukun’ (re: breadfruit chips). The fruit of A. altilis is rich of nutrition source the like carbohydrate, protein, less fat, some minerals, and essential amino acid. A. altilis is capable as potential future medicine and alternative food source, therefore more development about the study is still required.